Towards Inclusive Avatars: A Study on Self-Representation in Virtual Environments - Ribeiro, Ailton; Arouca, Murilo Guerreiro; Amorim, Ana Maria; Pestana, Maria Clara; Vieira, Vaninha (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2024: Anais do XIX Simpósio Brasileiro de Sistemas Colaborativos, 2024)
Avatars, digital representations of users in virtual environments, play a central role online, especially in the emerging context of the Metaverse. The customization of avatars provides individuals with the capability to craft personalized depictions, yet the process of self-representation is intricately influenced by various factors, encompassing identity, self-expression, and contextual considerations. However, there are gaps in research on the inclusive representation of avatars. This study investigates self-representation through avatars in virtual environments. We collected data through an online questionnaire with 133 participants. The findings are promising and underscore the need to make avatars more inclusive and representative, promoting diversity in virtual environments.